Bangers & Cash: Cutting red tape to put Britain at the centre of the cultivated meat revolution - Matthew Lesh (Institute of Economic Affairs (IEA), 2023)
Meat production has grown significantly in recent decades. It provides a source of protein and enjoyment to billions of people. Livestock farming raises significant issues for the environment, including greenhouse gas emissions, expansive land and water use, polluted ecosystems, and lost biodiversity; animal welfare from industrial practices; and health security, including infectious diseases. It will be difficult to reduce consumption of conventional meat, considering its popularity, through exposing the benefits of veganism or a 'meat tax'. The most effective response to the challenges associated with conventional meat is likely to be innovation that provides customers with a quality and affordable alternative. Cultivated meat is an alternative protein product produced in vitro using animal cells. It can taste the same, look the same and smell the same as conventional meat; presenting a solution to many of the challenges raised by conventional meat. Cultivated meat is different from plant-based products such as the Impossible Burger or Beyond Meat, which do not contain animal cells. In 2013, the first cultivated meat product, a burger, was presented to the world's media in London. In 2020, Singapore became the first country in the world to approve a cultivated meat product for sale to consumers, a chicken nugget from San Francisco-based start-up Eat Just. Cultivated meat start-ups have received substantial funding while, like other fast-moving innovations, the cost of production has declined by 99 per cent since the first demonstration a decade ago. The technology, however, could be held back by overregulation in the European Union and the United Kingdom. This is because of the EU's novel food regulations and their retention in UK law. The novel food regulatory process risks being too slow, creating significant uncertainties, and too cumbersome, resulting in producers seeking approval elsewhere. Brexit provides the opportunity for the UK to diverge from the EU's approach and introduce a regulatory regime that is more welcoming of food innovations such as cultivated meat. It could: - clarify and consult on requirements by establishing a Food Standards Agency (FSA) Advice Unit; - update the existing regulatory framework to prioritise innovation; - introduce a 'food sandbox'; and - recognise overseas approvals.
Keywords: 330; Meat products; Genetically engineered products; Novel foods; Food law; Deregulation; Brexit; United Kingdom; Fleischwaren; Gentechnisch erzeugtes Produkt; Neuartige Lebensmittel; Lebensmittelrecht; Deregulierung; Brexit; Großbritannien